2015
DOI: 10.1016/j.bjid.2014.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of human schistosomiasis in sub-Saharan Africa

Abstract: Schistosomiasis, a neglected tropical disease of poverty ranks second among the most widespread parasitic disease in various nations in sub-Saharan Africa. Neglected tropical diseases are causes of about 534,000 deaths annually in sub-Saharan Africa and an estimated 57 million disability-adjusted life-years are lost annually due to the neglected tropical diseases. The neglected tropical diseases exert great health, social and financial burden on economies of households and governments. Schistosomiasis has prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
267
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(295 citation statements)
references
References 63 publications
5
267
1
1
Order By: Relevance
“…15 With regards to LF, available recent reports indicate that in Africa, 34 countries are endemic, and Nigeria is believed to bear the highest burden of LF, with an estimated 80 to 120 million people at risk. [16][17][18] In a recent review article, Adenowo and colleagues 19 noted that schistosomiasis is the second most common neglected tropical disease after hookworm in SubSaharan Africa and accounts for 93% (192 million) of the world estimated 207 million cases of schistosomiasis with the highest prevalence of the infection seen in Nigeria (29 million). Adam and colleagues 20 observed that there is the growing recognition of the importance of developing concise materials and tools to communicate various types of information to policy-makers and those supporting them.…”
Section: Introductionmentioning
confidence: 99%
“…15 With regards to LF, available recent reports indicate that in Africa, 34 countries are endemic, and Nigeria is believed to bear the highest burden of LF, with an estimated 80 to 120 million people at risk. [16][17][18] In a recent review article, Adenowo and colleagues 19 noted that schistosomiasis is the second most common neglected tropical disease after hookworm in SubSaharan Africa and accounts for 93% (192 million) of the world estimated 207 million cases of schistosomiasis with the highest prevalence of the infection seen in Nigeria (29 million). Adam and colleagues 20 observed that there is the growing recognition of the importance of developing concise materials and tools to communicate various types of information to policy-makers and those supporting them.…”
Section: Introductionmentioning
confidence: 99%
“…Schistosome cercariae present water are known to lose their infectivity with time, (Adenowo et al, 2015). Interestingly, there was a significant association between infection with S. mansoni and going to the lake by the PSAC especially when the children accompany their parents/guardians or older children to the lake.…”
Section: Discussionmentioning
confidence: 99%
“…Use of the drug is mainly restricted to Brazil and South American countries but has been replaced by praziquantel as the principal drug and main line of treatment against schistosomiasis since the mid-2000s [24,25]. Artemisinin is an antimalarial drug which when used with artesunate and artemether combined has been shown to exhibit anti-schistosomal activity against juvenile worms [22]. However, the development of drug resistance in endemic areas against the Plasmodium strain has caused a bit of concern.…”
Section: Anti-schistosomal Drugsmentioning
confidence: 99%